POLA TANAM JAHE EMPRIT (Zingiber officinale Var. amarum) DENGAN BAWANG DAUN DAN KACANG MERAH DI KABUPATEN MAJALENGKA JAWA BARAT - Ermiati Ermiati (Pusat Penelitian dan Pengembangan Perkebunan, 2005)
Intercropping of Emprit Ginger (Zingiber officinale var. amarum) With Red bean and welsh onion in Majalengka District, West JavaThe experiment was conducted to study the appropriate intercropping which is technically feasible and economically profitable. The experiment was conducted at Cipanas, Werasari Village, Sub District Batarujek, District of Majalengka from November 2002 to August 2003. Evaluation of intercropping include as followed : I. Emprit Ginger (monoculture), II. Emprit Ginger + Welsh onion, III. Emprit Ginger + Red bean. Plant spacing for emprit ginger was 60 cm x 30 cm, while for welsh onion and red bean was 20 cm x 20 cm. Data collection for each intercropping include using of material used, labor, equipment and production of each commodities. Analyzed of input-out put and B/C ratio were used to determined the most efficient of intercropping. The results of experiment indicated that all of intercropping give a signi-ficantly of farmer income. The range of income was Rp. 2.297.700,- to Rp. 2.773.400,- per m2 with B/C ratio 2,3 -2,4. Intercropping of Emprit Ginger with Welsh onion gave the highest farmer income Rp. 2.773.400,- per m2 with B/C ratio 2,4. Then followed by intercropping of Ginger Emprit with Red bean Rp. 2.443.730,- with B/C ratio 2.3 and Monoculture of Emprit Ginger Rp. 2.297.700,- per m2. The highest income on intercropping of Emprit Ginger + Welsh onion and Emprit Ginger + Red bean may due to added income from welsh onion and red bean, although the cost production was also higher. By using model of intercropping system with welsh onion and red bean on Emprit Ginger production beside increase of farmer income, farmer also received added income before the main crop (ginger) harvested. It was also minimize the risk of failure of harvesting due to diseases attack.